2012
DOI: 10.1245/s10434-012-2389-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Bioinformatics and Clinicopathological Research of Gastrointestinal Stromal Tumors: Identification of Aurora Kinase A as a Poor Risk Marker

Abstract: By integrating bioinformatics and clinicopathological studies, AURKA was identified as a marker for high-risk GIST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 30 publications
4
31
0
Order By: Relevance
“…Moreover, by reanalyzing a dataset of GIST, our group identified aurora kinase A (AURKA), along with other cell cycle and mitosis genes, as a prognostic factor for recurrence. In addition, AURKA is a potential treatment target (38,39). Therefore, cell cycle regulation genes are a crucial group of potential biomarkers or targets in sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by reanalyzing a dataset of GIST, our group identified aurora kinase A (AURKA), along with other cell cycle and mitosis genes, as a prognostic factor for recurrence. In addition, AURKA is a potential treatment target (38,39). Therefore, cell cycle regulation genes are a crucial group of potential biomarkers or targets in sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…119 Accumulating data revealed that AURKA was frequently amplified and overexpressed in GC, 36,[120][121][122] and AURKA amplification associated with significantly worse survival. 123 A recent study showed copy number gains of AUKRA were detected in a relative high percentage of GC samples (30.5%). A positive connection has been found between AURKA amplification and tumor progression, 124 suggesting that AURKA may have prognostic significance.…”
Section: Chromosome 20mentioning
confidence: 98%
“…All eligible studies were published between 2005 and 2014. All TNM Stages (I-IV) were considered in 18 studies (46.2%) (9,18,20,27,28,30,(34)(35)(36)(37)(38)40,43,44,50,55,56,58), non-metastatic solid tumors (including Stage I-III or localized disease, based solely on singlestage disease or mixture of tumor stages) were considered in 12 (30.8%) studies (22,29,31,33,39,41,42,46,48,51,53,54); metastatic solid tumors (Stage IV) patients were considered in four studies (10.2%) (23,45,49,57); disease stage was not available were considered in five studies (12.8%). Four studies analyzing AURKA mRNA expression used real-time reverse transcription PCR (RT-PCR) (20,34,35,45); one study analyzing AURKA gene amplification by fluorescence in situ hybridization (FISH) (54); the other one used immunohistochemical (IHC) staining and RT-PCR (47); and the remaining 33 studies applied a immunohistochemistry detection method (9,18,19,21-23,27-33, 36-44,46,48-53,55-58).…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…Four studies analyzing AURKA mRNA expression used real-time reverse transcription PCR (RT-PCR) (20,34,35,45); one study analyzing AURKA gene amplification by fluorescence in situ hybridization (FISH) (54); the other one used immunohistochemical (IHC) staining and RT-PCR (47); and the remaining 33 studies applied a immunohistochemistry detection method (9,18,19,21-23,27-33, 36-44,46,48-53,55-58). Eight studies were conducted in patients from European countries (19,21,28,32,36,40,55,57), four in patients from USA (18,20,37,45), three in Oceania countries (33,46,49), one in South America (50), and twenty-three in Asian countries (9,22,23,27,(29)(30)(31)34,35,38,39,(41)(42)(43)(44)47,48,(51)(52)(53)(54)56,58). One or more oncologic outcome parameters were analyzed on multivariate analysis in 33 studies <...>…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%